2021
DOI: 10.1155/2021/5569961
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Plasma and Red Blood Cell Properties in Patients with Varicose Vein: A Pilot Study

Abstract: The varicose vein results from the inefficient functioning of the valves in the lower limb veins, making the blood flow slow down and leading to blood stasis and hypoxia. This type of vein dysfunction might be a result of the development of oxidative stress. We compared oxidative stress markers in the plasma and erythrocytes obtained from peripheral veins and varicose veins in the same patients (glutathione, nonenzymatic antioxidant capacity (NEAC), catalase (CAT) and acetylcholinesterase (AChE) activity, thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Leukocytosis is seen in patients with varicose veins and is an indicator of persistent inflammation with an increase in tissue hypoxia and a further increase in the hypoxia inducer factor to stimulate erythropoietin production and an additional increase in the RBC level of red blood cells in patients with varicose veins [32,33]. This persistent inflammation is confirmed by the elevation of the ESR level in patients with varicose veins [34][35][36][37].…”
Section: Discussionmentioning
confidence: 92%
“…Leukocytosis is seen in patients with varicose veins and is an indicator of persistent inflammation with an increase in tissue hypoxia and a further increase in the hypoxia inducer factor to stimulate erythropoietin production and an additional increase in the RBC level of red blood cells in patients with varicose veins [32,33]. This persistent inflammation is confirmed by the elevation of the ESR level in patients with varicose veins [34][35][36][37].…”
Section: Discussionmentioning
confidence: 92%
“…These changes were accompanied by a decrease in the activity of catalase (CAT) and acetylcholinesterase (AChE). We observed a decrease in the level of thiols in plasma, hemolysate, and plasma membranes, and an increase in parameters related to oxidative stress, such as the level of protein carbonyl compounds and the level of thiobarbituric acid reactive substances (TBARS) in varicose veins [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the level of oxidative stress parameters in plasma, e.g., TBARS, and protein carbonyls, as well as decreased catalase activity and thiol levels, were also observed in a group of patients with varicose veins compared to a group of healthy volunteers [151,152]. Oxidative damage to proteins and lipids was accompanied by a decrease in the level of thiols, a decrease in the level of non-enzymatic antioxidant capacity (NEAC), as well as a decrease in catalase, and acetylcholinesterase (AChE) activities in plasma derived from varicose veins [144]. It has been shown that the decrease in CAT activity can be initiated by hydroxyl radicals, superoxide, and H 2 O 2 , but not by organic peroxides [153,154].…”
Section: Antioxidants and Oxidative Stress In Plasma And Red Blood Ce...mentioning
confidence: 92%
“…We demonstrated that hemoglobin modified by ROS or bound to the plasma membrane is present in erythrocytes from the varicose vein [144]. It has been shown that irreversible oxidation of this cysteine residue, βCys93, in the globin chain may lead to the breakdown of the Hb structure and, consequently, the release of heme [145].…”
Section: Alterations In Red Blood Cells Properties In Cvedmentioning
confidence: 92%
See 1 more Smart Citation